Chemical Process Disturbance Compensation as a Fault Tolerant Control Problem. Issue 21 (2015) - Simani, S.; Farsoni, S.; Patton, Ron J.
Abstract: In general, the control of chemical processes that involve unknown disturbances presents interesting challenges. Research issues have been focused on detailed modelling of the involved phenomena in order to use e.g. robust on-line disturbance compensation procedures or attempting to cancel out the disturbance effect in the feedback control of the chemical system. However, the chemical modelling problem can remain a very difficult challenge due to the unknown or partially-known dynamics occurring in the process under investigation. Therefore, this article proposes a new approach to the disturbance compensation, which is recasted into the theory of robust fault estimation. The disturbances acting in the system can be thus viewed as faults with time-varying characteristics to be estimated and compensated within an output feedback fault-tolerant control scheme. In this way, the limitations arising from the use of model-based approaches are obviated. The unknown input estimation problem is hence embedded inside a control system with required stability and performance robustness. This can be a significant advantage over model-based unknown input compensation methods, in which the detailed modelling of the disturbance term can be essential, and for which robustness with respect to its characteristics is difficult to achieve using purely nonlinear modelling strategies.